Redefining action: facts and beliefs in the social world - Santamaría-Velasco, Freddy; Ruiz-Martínez, Simón (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2022)
This article presents a definition of action that links empirical facts with normative reasons to form an explanation of rational agency with predictive capabilities. This idea is developed along the lines of pragmatism which holds that a set of beliefs is a matter of linguistic evaluation from a particular community. This notion is related to the idea of facts as empirical information that is cognitively apprehended. Such information is regarded as an input which is later contrasted to expected (liable) behavioral responses from the agent. The deviation of such observed behavior with respect to the expected one represents an evaluative output that is understood as the definition of reasonably expected behavior. Action is, thus, understood as the outcome of such an evaluative process.